Mechanical and functional properties of polyamide/graphene nanocomposite prepared by chemicals free-approach and selective laser sintering. (December 2022) - Meng, Qingshi; Song, Xuyang; Han, Sensen; Abbassi, Fethi; Zhou, Zhiqiang; Wu, Bin; Wang, Xiangming; Araby, Sherif
Abstract: Selective laser sintering (SLS), an additive manufacturing process, provides new strategies for fabricating complex components with tailored mechanical, electrical and thermal properties. This work proposes an electrostatic driven self-assembly approach to prepare graphene platelets (GnPs)-coated polyamide (PA) nanocomposite powders for SLS process. Morphology and microstructure characterizations confirmed the synthesis of ∼3-nm-thick GnPs with high structural integrity which contributed to the mechanical properties, electrical and thermal conductivity of the nanocomposites. The study showed that unlike to traditional plastic processing methods, SLS process can develop strong and electrically conductive parts using only 0.2 wt% of GnPs; at this content, percolation threshold was observed (between 0.2 wt% and 1.0 wt%) and Young's modulus increased by 81%. This work indicates that introducing graphene platelets into SLS process is an effective approach in order to prepare polymer nanocomposites with high mechanical, electrical and thermal properties. Furthermore, a numerical model was developed to simulate the quasi-static mechanical behavior of the 3D printed neat PA and its GnP nanocomposites. The developed model is in accord with the experimental measurements; this would be a benchmark model to pre-design and predict the mechanical behavior of various profiles before 3D printing. Graphical abstract: Image 1 Highlights: Graphene platelets (GnPs) were succeeded to be coated on polyamide (PA) particles via electrostatic technique. Selective Laser Sintering (SLS) was used to manufacture PA/GnPs with high mechanical performance, and electrical and thermal conductivity. At 0.2 wt% GnPs, Young's modulus of PA increased by 81%; and electrical conductivity percolation threshold was observed. A numerical model was developed to simulate the quasi-static mechanical behavior of the 3D-printed PA/GnP nanocomposites.